教師專業地位的知識社會學分析：以英國課程發展為例On the Professional Status of Teachers in British Curriculum Development: A Sociological Analysis of - 王雅玄 Ya-Hsuan Wang (Higher Education Foundation, 2012)
本研究以英國1970年代課程發展動向作為觀察的基礎，並檢視當時課程研究的學術文獻，進而分析兩者的互動關係，提出教師在課程研究中所扮演的重要角色；接著從知識社會學的角度來關懷教育改革與課程發展脈絡下的教師專業地位，試圖分析各種不同觀看知識的取向與教師專業地位的關係，以瞭解教師在教學實踐上確保理論與實踐一致的關鍵何在。主要研究焦點有二：首先從課程發展的研究中探究教師地位、論述教師與課程的關係及教師的課程決定角色；接著從知識觀來檢視教師的專業地位，剖析1970年代以後英國課程社會學者的課程觀，如Bernstein、Lawton、Young、Eggleston、Goodson及Kelly，從中探討教師專業角色在落實教育改革中的重要地位。本研究獲致結論如下：第一，在中央控制課程的脈絡下，教師是附屬地位，持有「無脈絡課程觀」，教師無需詮釋課程，亦無影響課程的權力；教師巨觀看待課程內容（what）的知識觀，對課程僅能持「接受觀點」。第二，在學校本位課程的脈絡下，教師是夥伴地位，持有「脈絡化課程觀」，教師以自身觀點詮釋課程知識，可能符應巨觀社會政治文化歷史脈絡；著重教師如何解釋巨事敘述的知識觀（how），對課程持有「反身觀點」。第三，在教師發展課程的脈絡下，教師是專業地位，持有「再脈絡化課程觀」，教師重新賦予課程新的脈絡，有主導課程知識的權力，詢問課程哲理的知識觀（why），對課程持有「重構觀點」。第四，孩童觀點的內省性課程哲學將是未來課程研究發展的重點。knowledge appeared after the 1970s, such as B.Bernstein, D. Lawton, M. Young, J. Eggleston, I. Goodson, A. V. Kelly. In conclusion, there are different perspectives on teacher role in different context of curriculum reform. Firstly, for a central controlled curriculum, teachers usually receive official curriculum with the macro view on knowledge, and they, taking an underpart role with context-proof curriculum perspective, have no power to influence or interpret curriculum. Secondly, for a school-based curriculum, teachers take a partnership role to explain how the school curriculum is run under the socio-economic context. Thirdly, for teacher-based curriculum, teachers take a professional role to recontextualise the curriculum with a reconstructive perspective by asking why the school curriculum is constructed. Finally, the approach to the sociology of knowledge after 1970s proposes teachers as cultural reflexive practitioners. Teachers should conduct reflexive researches to develop the ability of reflecting themselves and examining their own discourses critically.